Spatio-temporal distribution of mosquitoes and risk of malaria infection in Rwanda - Hakizimana, Emmanuel; Karema, Corine; Munyakanage, Dunia; Githure, John; Mazarati, Jean Baptiste; Tongren, Jon Eric; Takken, Willem; Binagwaho, Agnes; Koenraadt, Constantianus J.M. (Acta tropica, 2018)
To date, the Republic of Rwanda has not systematically reported on distribution, diversity and malaria infectivity rate of mosquito species throughout the country. Therefore, we assessed the spatial and temporal variation of mosquitoes in the domestic environment, as well as the nocturnal biting behavior and infection patterns of the main malaria vectors in Rwanda. For this purpose, mosquitoes were collected monthly from 2010 to 2013 by human landing catches (HLC) and pyrethrum spray collections (PSC) in seven sentinel sites. Mosquitoes were identified using morphological characteristics and PCR. Plasmodium falciparum sporozoite infection rates were determined using ELISA. A total of 340,684 mosquitoes was collected by HLC and 73.8% were morphologically identified as culicines and 26.2% as anophelines. Of the latter, 94.3% were Anopheles gambiae s.l., 0.4% Anopheles funestus and 5.3% other Anopheles species. Of An. gambiae s.l., An. arabiensis and An. gambiae s.s. represented 84.4% and 15.6%, respectively. Of all An. gambiae s.l. collected indoor and outdoor, the proportion collected indoors was 51.3% in 2010 and 44.9% in 2013. A total of 17,022 mosquitoes was collected by PSC of which 20.5% were An. gambiae s.l. and 79.5% were culicines. For the seven sentinel sites, the mean indoor density for An. gambiae s.l. varied from 0.0 to 1.0 mosquitoes/house/night. P. falciparum infection rates in mosquitoes varied from 0.87 to 4.06%. The entomological inoculation rate (EIR) ranged from 1.0 to 329.8 with an annual average of 99.5 infective bites/person/year. This longitudinal study shows, for the first time, the abundance, species composition, and entomological inoculation rate of malaria mosquitoes collected throughout Rwanda.